From Allergen Molecules to Molecular Immunotherapy of Nut Allergy: A Hard Nut to Crack - Fuhrmann, Verena; Huang, Huey-Jy; Akarsu, Aysegul; Shilovskiy, Igor; Elisyutina, Olga; Khaitov, Musa; van Hage, Marianne; Linhart, Birgit; Focke-Tejkl, Margarete; Valenta, Rudolf; Sekerel, Bulent Enis (Frontiers in Immunology, 2021)
Peanuts and tree nuts are two of the most common elicitors of immunoglobulin E (IgE)-mediated food allergy. Nut allergy is frequently associated with systemic reactions and can lead to potentially life-threatening respiratory and circulatory collapse. Furthermore, nut allergy is rarely grown out. Whether sensitized patients exhibit severe and life-threatening reactions (e.g., anaphylaxis), mild and/or local reactions (e.g., pollen-food allergy syndrome) or no relevant symptoms depends much on IgE recognition of digestion-resistant class I food allergens, IgE cross-reactivity of class II food allergens with respiratory allergens and clinically not relevant plant-derived carbohydrate epitopes, respectively. Accordingly, molecular allergy diagnosis based on the measurement of allergen-specific IgE levels to allergen molecules provides important information in addition to food allergen provocation testing in the diagnosis of food allergy. Molecular allergy diagnosis helps identifying the genuinely sensitizing nut, it determines IgE sensitization to class I and II food allergen molecules and hence provides a basis for personalized forms of treatment such as precise prescription of diet and allergen-specific immunotherapy (AIT). Currently available forms of nut-specific AIT are based only on allergen extracts, have been mainly developed for peanut but not for other nuts and, unlike AIT for respiratory allergies which utilize often subcutaneous administration, are given preferentially by the oral route. Here we review prevalence of allergy to peanut and tree nuts in different populations of the world, summarize knowledge regarding the involved nut allergen molecules and current AIT approaches for nut allergy. We argue that nut-specific AIT may benefit from molecular subcutaneous AIT (SCIT) approaches but identify also possible hurdles for such an approach and explain why molecular SCIT may be a hard nut to crack.